Complete mitochondrial genome of the freshwater monogonont rotifer Brachionus rubens (Rotifera, Brachionidae). Issue 1 (2nd January 2020) - Choi, Beom-Soon; Lee, Young Hwan; Lee, Jin-Sol; Ogello, Erick O.; Kim, Hee-Jin; Hagiwara, Atsushi; Lee, Jae-Seong
Abstract: The two complete mitochondrial genomes were sequenced from the freshwater monogonont rotifer Brachionus rubens . The genome sequences were 12, 041 bp and 13, 793 bp in size, and the gene order and contents were identical to those of the freshwater rotifer B. rubens China, but were different in three tRNA-Arg, tRNA-Ile, and tRNA-Leu between both B. rubens mitochondrial genomes, while B. calyciflorus had peculiar gene order in mitochondrial DNA I. Of 12 protein-coding genes (PCGs), one gene ( ND5 ) had incomplete stop codons. Furthermore, the start codon of ND4 and CO2 gene was ATT, while the start codon of other PCGs was ATG. The base composition of 12 PCGs in B. rubens mitogenome showed 22.5% for A, 46.5% for T, 16.3% for C, and 14.7% for G, respectively.